The role of vowel formant frequencies and duration in the perception of foreign accent. Issue 1 (2nd January 2017) - Chan, Kit Ying; Hall, Michael D.; Assgari, Ashley A.
ABSTRACT: This study used synthesis to manipulate vowel formant frequencies and durations to evaluate their role on foreign accent perception. Formant frequencies and durations for the vowels /æ/, /ʌ/, and /a/ were manipulated with changes toward and away from the mean native English and Spanish-accented values from Sidaras, S. K., Alexander, J. E. D., & Nygaard, L. C. (2009. Perceptual learning of systematic variation in Spanish-accented speech. The Journal of the Acoustical Society of America, 125, 3306–3316). Native listeners rated these stimuli on degree of accentedness and comprehensibility. Gradual changes in formant frequencies from native to non-native values impacted /a/ negatively, /ʌ/ positively, and /æ/ minimally. Effects of vowel duration on either type of ratings were small and restricted to vowel-specific interactions. The current findings suggest that vowel formant frequencies are primary cues to foreign accent. Their influence depends upon whether or not frequencies could reflect alternative vowel categories.